Development, Characterization and Dissolution Study of Solid Dispersion of Diclofenac Sodium by Kneading Technique - Singh, Gajendra; Khinchi, M.P.; Agrawal, Dilip; Sharma, Natasha; Hussain, Adil (Asian Journal of Pharmaceutical Research and Development, 2013)
The present investigation was aimed to dissolution enhancement of diclofenac sodium by using Solid dispersion Technique using Mannitol, Sodium starch glycolate,Polymer.using in this technique. Solid dispersion are done by kneading method and solvent evaporation method..The solid dispersion characterized by particle size analysis,Drug content, in vitro and in vivo pharmacokinetic studies. .Highest dissolution is found in f 1 formulation in Phosphate buffer Ph 6.8 as compared to other formulation.